THE EFFECT OF PROMOTION AND PRICE AT SHOPEE ON THE PURCHASE DECISION OF COSMETIC PRODUCTS IN MANADO - Warouw, Aurilia; Mangantar, Maryam; Rogi, Mira (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to examine the effect of promotion and price at Shopee on the purchase decision of Cosmetic products in Manado. The research employs a quantitative approach. The population in this study are Manado city residents who has been using Shopee with the number of samples of 100. The data collection technique used in this study was the questionnaire and measured using the Likert Scale. The variables studied include promotion, price, and purchase decision. Data analysis is conducted using multiple linear regression analysis, using the IBM SPSS 30 to determine the effect of promotion and price on the purchase decision. The results of this study state that Promotion and Price partially have a positive effect on Purchase Decision of Cosmetic Products at Shopee, and then simultaneously Promotion and Price have a poositive effect on Purchase Decision of Cosmetic Products at Shopee.   Keyword: Promotion, Price, Purchase Decision